1984
DOI: 10.1159/000176803
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein-Dependent Modification of Serum Cholesterol Level in Rats

Abstract: Male rats were fed for 4 weeks cholesterol-free diets containing proteins from different sources, milk, fish, egg yolk, soybean, rice and peanut. The antihypercholesterolemic effect of vegetable proteins compared to animal proteins was certified. There was a negative correlation (γ = -0.74) between the serum cholesterol level and the arginine/lysine ratio of dietary protein, suggesting a role of this ratio in determining the serum cholesterol level. In general, the fasting level of circulating insulin was lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 16 publications
(29 reference statements)
4
38
0
1
Order By: Relevance
“…Soybean protein was reported to have anti-hyperlipidemic effect because it can inhibit CH absorption and increase neutral steroids (Potter, 1995), and excrete bile acid (Sugano et al, 1984). LSB can also lower CH and increase the excretion of fecal nitrogen compounds and fecal neutral steroids according to our observations.…”
Section: Resultssupporting
confidence: 70%
“…Soybean protein was reported to have anti-hyperlipidemic effect because it can inhibit CH absorption and increase neutral steroids (Potter, 1995), and excrete bile acid (Sugano et al, 1984). LSB can also lower CH and increase the excretion of fecal nitrogen compounds and fecal neutral steroids according to our observations.…”
Section: Resultssupporting
confidence: 70%
“…This ratio is lower than that of many fishery products such as Channa striatus (1.64, Zuraini et al, 2006), Pampus punctatissimus (1.49; Zhao et al, 2010) Clarias anguillaris (1.05; Adeyeye, 2009). Worthily, it has been reported that this low ratio reduced concentrations of cholesterol in the serum and aorta and has hypocholesterolemic effects (Sugano et al, 1984;Rajamohan et al, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…Finally after diaminobenzidine treatment the sections were mounted properly and examined. Statistical analysis of the results was performed using one way layout ANOVA and Duncan's multiple-range test (Sugano et al 1984).…”
Section: Methodsmentioning
confidence: 99%